Estratégias de leitura : conhecimento acionado nas interações discursivas, produzidas por crianças e professora-pesquisadora durante a leitura compartilhada - Severo, Maiara Foli (2019)
The research that originated this dissertation aimed to analyze the discursive interactions produced by students and their teacher, focusing on the reading strategies triggered / taught as a response to the problems that stand in the way of understanding a text read during the shared reading activity. The problem that guided the research is formulated as follows: How can shared reading give readers in training the use of reading strategies so that certain decisions can be made to solve the challenges that texts pose?The theoretical and methodological principles that supported it were formulated based on Solé (1998), Kleiman (1997; 2008), Smith (1989), Bakhtin (2003), Bakhtin / Volochinov (2010), Colomer (2007), Girotto and Souza (2010) and Abarca and Rico (1998). From a qualitative approach, research benefits from the methodological principles of action research and autoscopy. The fieldwork was carried out with a private school in the city of Passo Fundo / RS, with children aged 7 to 8 years. For data production, video recordings, transcription of the video file and the elaboration of the field research protocol were performed. During the shared reading sessions, the research-teacher and students published the book The Extraordinary Journey of Edward Tulane by Kate DiCamillo. The analysis of the selected scenes allowed us to recognize that, among the strategies triggered by the children during the shared reading, were: preparation of predictions; formulating questions to solve challenges; production of inferences to substantiate or refute hypotheses; identification of the main idea; resumption of content already read and for checking forecasts; paraphrase production; abstract writing. Many of these strategies need the teacher's intervention, by requesting predictions and resuming the text and predictions, proposing questions to raise doubts and challenges. It is also responsible for the management of reading so that the spaces for discussion and listening are guaranteed. Understanding the text in shared reading is collectively constituted in an intense process of interaction in which speakers and listeners actively participate in the dialogue.